INFRARED DRYING CHARACTERISTICS OF JERUSALEM ARTICHOKE SLICES - Doymaz, Ibrahim (YILDIZ TECHNICAL UNIV, 2017)
In this study, drying characteristics of Jerusalem artichoke slices were investigated by using infrared technique. The Jerusalem artichoke slices were dried at 62, 74, 88, 104 and 125 W infrared power levels. An increase in the infrared power resulted in a significant reduction in the drying time. Lewis, Henderson and Pabis, Logarithmic, Midilli and Kucuk, and Wang and Singh models were used to fit experimental data. The Midilli and Kucuk model has been determined to be the best model that represents the experimental data. Effective moisture diffusivity values ranged from 4.81x10(-10) m(2)/s to 1.97x10(-9) m(2)/s, and increased with the increase in infrared power. The activation energy was calculated as 6.74 kW/kg.
Keywords: Activation energy; effective moisture diffusivity; infrared drying; Jerusalem artichoke; mathematical modelling; MOISTURE DIFFUSIVITY; VACUUM CONDITIONS; KINETICS; MICROWAVE; ENERGY; LEAVES; L.; BEHAVIOR; QUALITY; DRYER; Engineering